Immigration and educational spillovers: Evidence from Sudeten German expellees in post-war Bavaria - Alexandra Semrad (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
This paper analyses long-term effects of forced WWII migration on educational outcomes. Specifically Sudeten German expellees in post-war Bavaria coming from highly industrialized Sudetenland (Czechoslovakia) had strong preferences for higher secondary schooling, especially in form of a practical, business-related, and general education school. As a result they became actively engaged in the development of post-war middle track education (Realschule, Fachschule). Employing county-level data on student numbers and graduates of secondary education, empirical analysis including ordinary least squares, instrumental variable, and differences-in-differences models reveals that counties housing a higher share of Sudeten Germans after the war are significantly associated with higher educational development some 20 years later. An increase in the share of Sudeten Germans by 1 percentage point increases the share of children (graduates) in middle track education by at least 0.8 (0.1) percentage points, respectively. Calculations suggest that these effects are not mechanically caused by Sudeten Germans and their children demanding education, but are the actual result of educational spillovers to the local population.
urn:nbn:de:bvb:19-epub-24851-6
Keywords: I29; N34; O15; 330; Educational spillovers; Forced migration; Post-war Bavaria